The nuclear envelope: LINCing tissue mechanics to genome regulation in cardiac and skeletal muscle. (8th July 2020) - Piccus, Rachel; Brayson, Daniel
Abstract : Regulation of the genome is viewed through the prism of gene expression, DNA replication and DNA repair as controlled through transcription, chromatin compartmentalisation and recruitment of repair factors by enzymes such as DNA polymerases, ligases, acetylases, methylases and cyclin-dependent kinases. However, recent advances in the field of muscle cell physiology have also shown a compelling role for 'outside-in' biophysical control of genomic material through mechanotransduction. The crucial hub that transduces these biophysical signals is called the Linker of Nucleoskeleton and Cytoskeleton (LINC). This complex is embedded across the nuclear envelope, which separates the nucleus from the cytoplasm. How the LINC complex operates to mechanically regulate the many functions of DNA is becoming increasingly clear, and recent advances have provided exciting insight into how this occurs in cells from mechanically activated tissues such as skeletal and cardiac muscle. Nevertheless, there are still some notable shortcomings in our understanding of these processes and resolving these will likely help us understand how muscle diseases manifest at the level of the genome.